Reflecting on the Impact of Covid-19 Pandemic on Businesses, Minority Groups and their Implications for Socio-economic wellbeing in Britain - Ofori, Felix Nana Kofi (Archives of Business Research, 2021)
This article examined the impact of Covid-19 on businesses through the prism of the British government’s strategic policies to stem the pandemic. It argues that the pandemic has paralysed major sectors of the national economy through locked-down measures, which consequently restricted the people’s socio-economic welfare. Also, the article contends that the retailing and pubs sectors of the economy registered dwindled revenue and created shortages of employment in the country. With major terminals of the British Airports shut down, the article demonstrates that several employment opportunities, spanning air stewardess, airport security, cargo handling, restaurants and retailing were stifled. In addition, the article proposes that, the general social and economic fabrics of workers in the aviation industry, majority of whom, belonged to the minority communities were restricted. On the minority groups, the article states that they represent the most afflicted and marginalized population during the pandemic; because, they were easily targeted for redundancies and furlough schemes without the needed representation at executive levels to protect their interests. Regarding the government’s strategies, the article argues that although it implemented political and economic solutions to support businesses and protect families, in order to absolve them from the crises, the major concern was that the measures were late and failed to adequately address the crisis. With respect to perspectives, the article points out that, though furlough schemes and soft loans were provided to guarantee the safety of businesses and citizens; the manner of implementation by the government was not creative enough to resolve the crisis. Lastly, the article argues that regardless of the government‘s policies to redeem thousands of businesses and families from socio-economic distresses, minority groups in Britain were largely disadvantaged, thereby reinforcing the status-quo